The implications of globalization for textbooks of French as a foreign language from the beginning of the 21st century - Schmitt, Francois (Romanica Olomucensia, 2019)
Globalization, which concerns all aspects of material, cultural, and social life, is giving rise to a new kind of transnational cosmopolitism that is more and more detached from its national ties and which has as its cultural reference the world culture that is common to the whole of human society, beyond national differences. Globalization has a huge impact on the didactics of French as a foreign language, which reacts to this impact by liberating itself from its national framework. Now language is considered as a global product liberated from its national ties and the learner is seen as a player in transnational globalization. The impact of globalization on the didactics of French as a foreign language, if thus defined, appears prominently in contemporary French in foreign language textbooks, which devote a significant role to elements which are not connected to French-speaking culture through fictional characters, places, or cultural references.
Keywords: culture; French as a foreign language; globalization; multicultural; textbook; transcultural